A Comprehensive Review of Garbha Samskara on Mother and Progeny - Current Need for Integrated Pregnancy Care Practices - Sanikop, Girija M.; Huilgol, Pooja (Journal of Neonatal Surgery, 2025)
Garbha Samskara encompasses practices/regimes that focus on the physical and psychological developmental aspects, both in the mother and the foetus, through nutritional and behavioural interventions. Understanding the specific impact of each Garbha Samskara can aid obstetricians in recommending appropriate regimen to pregnant women, who may be prone to pregnancy-related complications. This review is aimed to understand the impact of each Garbha Samskara by studying them with an inclusive approach and to identify potential indicators to assess their impacts. Ayurveda and contemporary literature and reviews from various available meta-analyses, systemic reviews, and clinical research procured from PubMed, Google Scholar, DHARA databases and Ayurveda texts were studied. Search keywords like ‘Garbha Samskara’, ‘Garbhini Paricharya’, ‘Garbhini AND assessment’, ‘Ayurveda AND antenatal-care’ and terms specific to each Garbha Samskara were used. The related researches were studied. Based on this review, it can be deduced that these regimens may potentially execute protective action on the mother and foetus by preventing stress, anxiety, pregnancy-related disorders and, post-delivery complications. They ease the mode of delivery and they are capable of instilling desired values in the child to be born. Using suitable parameters, it is possible to assess and document the impact of each Garbha Samskara. The integrated practice of Garbha Samskara may have the potential to reduce the maternal mortality ratio (MMR) and prevent nutrition-related disorders in the mother and foetus. Since Garbha Samskara is a cost-effective therapy, it can be easily integrated into maternal and child welfare programs established by the government due to its accessibility and affordability.